Analysing the Life Satisfaction of Risk-averse and Risk-loving Investors in South Africa - Shenjere, PA; Ferreira-Schenk, SJ (International Journal of Economics and Financial Issues, 2024)
Financial well-being is normally referred to as a person’s contentment with their financial situation. The level of life satisfaction among investors may vary depending on factors such as their risk tolerance and demographics. Demographic variables such as age and gender may influence an investor’s life satisfaction, which, in turn, could influence their financial decisions. Furthermore, an investor’s willingness to take risks can also affect financial decisions, ultimately influencing their life satisfaction. The objective of this paper is to identify and determine the influence of demographics and risk tolerance levels on individual investor life satisfaction. Secondary data were obtained in the private domain from an investment company that collected 1 059 from its client base. The results of this research paper indicated that there is a significant difference between the satisfaction of life of risk-averse and risk-loving investors. Risk-averse investors showed a negative relationship with life satisfaction, while risk-loving investors showed a positive relationship. This meant that the more risk-averse investors were, the lower the life satisfaction, indicating that high life satisfaction was accompanied by high risk. A significant difference was also found between life satisfaction and age and gender. Male investors were more satisfied with their lives than female investors. Older investors experienced higher levels of life satisfaction compared to investors in other age groups. As a result, these findings will make a considerable contribution to the way financial managers create investment portfolios for their clients.